KEEFEKTIFAN PENDEKATAN PROBLEM POSSING SETTING KOOPERATIF TIPE THINK PAIR SHARE DI SMPN 1 MAKASSAR - Liani, Ahyani Mirah; Abidin, Muhammad Rais; Umar, Ramli (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
The quality of mathematics education in Indonesia is still low when compared to the quality of mathematics education in several countries, so it is necessary to improve the quality by developing effective learning models for teachers and students. This study aims to see the level of effectiveness of the think pair share cooperative learning model in improving student learning outcomes. This research method uses an experimental research approach which was carried out at Junior Hihg School 1 Makassar by conducting post and pre tests to identify student learning outcomes and activities. The results showed that there were differences in the results after the posttest and pretest where there was an increase in the average score with the standard deviation increasing from 3.4 to 6.6 while the students' activities got a score of 3.7 with a very good category. Therefore, it can be concluded that the application of the think-pair-type cooperative learning model.